Who gets the biggest bang for the buck? A review of minimum wage and purchasing power in prison commissaries versus superstores - Zgoba, Kristen M. (Journal of crime and justice, 2020)
One of the often-noted ‘pains of imprisonment’ is the deprivation of good and services. One of the few ways that prisoners can acquire additional amenities is to purchase items at the prison commissary. As such, the commissary represents a small amount of control that inmates have over their lives with regard to food, clothing, and methods to pass the time. To use the commissary, however, inmates must have money in their accounts; typically from their institutional job or via family members or friends. The present study seeks to examine the prices of commissary items along with typical institutional minimum wage salaries of inmates, to determine the likelihood of inmates purchasing from the commissary. In addition, items of similar size and convenience from the commissary are compared with prices found online in a large superstore and federal and state minimum wages are compared to examine buying power. The authors find that contrary to common belief, prices of items in the commissary are similar to superstores in the free community; however, in-prison wages are so low that it is unlikely inmates can afford to purchase many, if any amenities without supplemental financing from families and friends. Implications of these findings are discussed.